Relationship of aerobic and anaerobic parameters with 400 m front crawl swimming performance - Kalva-Filho, C. A.; Campos, E.Z.; Andrade, V. L.; Silva, A. S. R.; Zagatto, A. M.; Lima, M. C. S.; Papoti, M. (Biology of Sport, 2015)
The aims of the present study were to investigate the relationship of aerobic and anaerobic parameters with 400 m performance, and establish which variable better explains long distance performance in swimming. Twenty-two swimmers (19.1±1.5 years, height 173.9±10.0 cm, body mass 71.2±10.2 kg; 76.6±5.3% of 400 m world record) underwent a lactate minimum test to determine lactate minimum speed (LMS) (i.e., aerobic capacity index). Moreover, the swimmers performed a 400 m maximal effort to determine mean speed (S400m), peak oxygen uptake ( · VO2PEAK) and total anaerobic contribution (CANA). The CANA was assumed as the sum of alactic and lactic contributions. Physiological parameters of 400 m were determined using the backward extrapolation technique ( ·V O2PEAK and alactic contributions of CANA) and blood lactate concentration analysis (lactic anaerobic contributions of CANA). The Pearson correlation test and backward multiple regression analysis were used to verify the possible correlations between the physiological indices (predictor factors) and S400m (independent variable) (p<0.05). Values are presented as mean ± standard deviation. Significant correlations were observed between S400m (1.4±0.1 m.s-1) and LMS (1.3±0.1 m.s-1; r=0.80), · VO2PEAK (4.5±3.9 L.min-1; r=0.72) and CANA (4.7±1.5 L·O2; r= 0.44). The best model constructed using multiple regression analysis demonstrated that LMS and · VO2PEAK explained 85% of the 400 m performance variance. When backward multiple regression analysis was performed, CANA lost significance. Thus, the results demonstrated that both aerobic parameters (capacity and power) can be used to predict 400 m swimming performance.